Clinical study of complications of a peripherally inserted central catheter in cancer patients - André Luis Victor Bonfim; Germana Alves deBrito; Aline Lourenço Baptista; Luis André Silvestre Andrade; Marina Harume Imanishe; Benedito Jorge Pereira (Wiley, 2023)
Abstract Aim To evaluate complications after PICC use in cancer patients. Design This was a clinical and retrospective study in which the risk factors and complications of PICC use were evaluated. Methods This study was carried out in the patient, emergency room, and intensive care units through the evaluation of electronic medical records. To assess the association between qualitative variables, the chi‐squared test or Fisher's exact test was used, and to compare the reason for withdrawal, the Kruskal-Wallis test was applied. Results A total of 359 patients (53.5% men) with 43.1 ± 14 years who had a PICC (88% with solid tumours) were evaluated. The most common complications were mechanical complications (61.2%), infection (38%), and thrombosis (57.1%). Patients with double‐lumen catheters experienced thrombosis (85.7%). This study demonstrated the effectiveness of PICC and that patients with haematological cancer are more prone to multiple PICC passages and more mechanical complications and infections.